Evaluation of Indigenous Fynbos and Renosterveld Species for Cover Crop Management in the Vineyards of the Coastal Wine Grape Region, South Africa - Fourie, J.C. (South African Journal of Enology and Viticulture, 2016)
Four treatments in which fynbos and renosterveld species were employed as cover crops, and two treatments in which exotic species were used as cover crops, were applied. A treatment in which indigenous annuals and an exotic annual was sown as a mixture, and a control in which no cover crop was established, were also included in the trial. These eight treatments were applied for four consecutive years on a sandy soil (33o52’S, 18o58’E) and a sandy loam soil (33o55’S, 18o52’E) in vineyards near Stellenbosch, South Africa. Effective suppression of the winter growing weeds was achieved with Avena sativa L. cv. Pallinup on a sandy soil from the third season onwards. This was also achieved with a mixture of Ornithopus sativus L. cv. Emena (50%) and three indigenous broadleaf annuals (50%), namely Felicia heterophylla (Cass) Grau, Dimorphotheca pluvialis (L.) Moench and Scenecio elegans L. None of the renosterveld and lowland fynbos mixtures or monocultures had the ability to become established effectively on both the sandy and sandy loam soil, or could compete effectively with the winter-growing weeds commonly found in the vineyards of the Coastal wine grape region of the Western Cape. These species therefore should not be considered for cover crop management in this region.